2018
DOI: 10.7812/tpp/17-216
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Abnormal Vitamin D Levels in Athletes

Abstract: Vitamin D is a lipophilic prohormone integral to musculoskeletal, autoimmune, oncologic, cardiovascular, and mental health. Of particular importance to the orthopedic surgeon is the role of vitamin D in the regulation of bone mass, muscle strength, and physical performance. Although vitamin D-related skeletal pathologies are rare in industrialized nations, emerging research in the field has shown that most American adults have inadequate levels of vitamin D. Even among athletes, there is a high prevalence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…It was found that the athletes participating in the study used the most supplements containing vitamin D, multi-vitamin, and omega-3, respectively, to strengthen their immunity against COVID-19. The importance of vitamin D in the athlete's health and performance has been the subject of many studies, especially in recent years [39,40]. The attitudes of the young people participating in the study are the reflection of their knowledge on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the athletes participating in the study used the most supplements containing vitamin D, multi-vitamin, and omega-3, respectively, to strengthen their immunity against COVID-19. The importance of vitamin D in the athlete's health and performance has been the subject of many studies, especially in recent years [39,40]. The attitudes of the young people participating in the study are the reflection of their knowledge on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the mechanisms underlying this association have to do with the known role of 25(OH)D or its metabolites in the regulation of genes and signaling pathways involved in calcium and phosphate homeostasis, as well as the proliferation and differentiation of skeletal muscle cells [57,58]. Vitamin D controls the initiation of muscular regeneration by promoting an increase of the cross-sectional area of skeletal muscle fibers through modulatory actions on the cell cycle of the skeletal tissue [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…25(OH)D deficiency is highly prevalent in both the general [ 12 ] and the athletic population [ 16 , 71 , 72 ], where professional athletes have a high prevalence of 25(OH)D deficiency [ 73 ]. The surprisingly high prevalence of inadequate 25(OH)D levels in athletes depends on different factors such as the geographic location, the time of day and year, the local climate conditions, and the sports disciplines (i.e., indoor vs. outdoor) [ 74 ].…”
Section: Consequences Of a 25(oh)d Deficiency In Sport—stress Fracmentioning
confidence: 99%
“…Preventative measures for spontaneous insufficiency fractures include—among others—the supplementation of 25(OH)D in athletes with 25(OH)D insufficiency [ 80 ]. It is recommended to treat athletes with insufficient or deficient 25(OH)D levels with 25(OH)D [ 16 ]. In case of a 25(OH)D insufficiency, normal blood levels of ≥30 ng/mL may be restored by optimizing the athlete’s lifestyle and, if appropriate, by oral substitution of 25(OH)D. This concentration of ≥30 ng/mL is associated with a protective effect and an enhancement of physical performance [ 74 ].…”
Section: 25(oh)d Supplementation As a Preventive Measurementioning
confidence: 99%
See 1 more Smart Citation